Analisis Harga Pokok Produksi Metode Full Costing Pada UMKM Nasi Cokot Mak’e Jakarta Selatan - Zulfani, Nur Agny; Sehati, Dewi Ulung Mangku; Syahidah, Hannifah; Nugraha, Andika Dwi; Witono, Muhammad Karim; Lestari, Tri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Nasi Cokot Mak'e is a Micro, Small, and Medium Enterprise (MSME) operating in the culinary industry, specializing in conveniently packaged, ready-to-eat rice accompanied with traditional side dishes. This study is to examine the calculation of production costs at MSME Nasi Cokot Mak'e utilizing the full costing approach. This research employs a qualitative descriptive method,, utilizing data collection approaches including interviews, observations, and documentation. The primary emphasis of the study is the application of the full costing approach to compute the entirety of production costs. The results show that Nasi Cokot Mak’e has so far used a simple calculation method that does not include all detailed components of production costs. Based on the full costing method, the total production cost in April 2025 amounted to IDR 15,740,000 for 4,500 portions, resulting in a cost of goods manufactured of IDR 3,500 per portion. In contrast, the internal business calculation only recorded IDR 12,105,000 or IDR 2,700 per portion. The difference of IDR 800 per portion shows that a more accurate and comprehensive calculation has been achieved through the application of the full costing method for better selling price determination and business decision-making in the future